Taṭwīr al-Wasā’il al- Ta‘līmīyah fī Dars ‘Ilm al-Balāghah bi-Istikhdām Barnāmij Lectora Inspire fī Ma‘had Darussalam Gontor, Ponorogo - Mabruroh; Aulia Gustiana (Universitas Negeri Jakarta, 2020)
This study aims to develop learning media for ‘ilm al-Balāghah (the science of Arabic rhetoric) using Lectora Inspire at Pondok Modern Darussalam Gontor, Ponorogo. Lectora Inspire is an electronic learning (e-learning) development application. This application is used to create online training courses, assessments, and presentations. Pondok Modern Darussalam Gontor has developed the curriculum of ‘ilm al-Balāghah, to be spesific ‘ilm al-Bayān, ‘ilm al-Ma‘ānī, and ‘ilm al-Badī‘. The students of the third semester in Kullīyat al-Mu‘allimāt al-Islāmīyah are considered from the stage in which they start learning ‘ilm al-Balāghah, especially ‘ilm al-Bayān, to encourage the language towards students in the Arabic language. The results of this study indicate that the tendency of students and their ability to learn ‘ilm al-Balāghah is lacking. This is evidenced by the low written test scores. Also, students face several problems in their learning, specifically, they feel learning difficulties and boredom. To overcome these problems, researchers decided to design learning media using the Lectora Inspire to attract interest the students for learning ‘ilm al-Balāghah.